2001
DOI: 10.1051/0004-6361:20010993
|View full text |Cite
|
Sign up to set email alerts
|

Spherical collapse of supermassive stars: Neutrino emission and gamma-ray bursts

Abstract: Abstract. We present the results of numerical simulations of the spherically symmetric gravitational collapse of supermassive stars (SMS). The collapse is studied using a general relativistic hydrodynamics code. The coupled system of Einstein and fluid equations is solved employing coordinates adapted to a foliation of the spacetime by means of outgoing null hypersurfaces. The code contains an equation of state which includes effects due to radiation, electrons and baryons, and detailed microphysics to account… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 26 publications
4
72
2
Order By: Relevance
“…Similarly, numerical studies on black hole formation have also been produced recently (e.g., Fryer 1999;Linke et al 2001;Fryer et al 2001, hereafter FWH01;Sekiguchi & Shibata 2005, hereafter SS05;Nakazato et al 2006, hereafter NSY06;Sumiyoshi et al 2006, hereafter SYSC06). Fryer (1999) classified core collapse into three types: (a) Stars with M P 25 M make explosions and produce neutron stars.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, numerical studies on black hole formation have also been produced recently (e.g., Fryer 1999;Linke et al 2001;Fryer et al 2001, hereafter FWH01;Sekiguchi & Shibata 2005, hereafter SS05;Nakazato et al 2006, hereafter NSY06;Sumiyoshi et al 2006, hereafter SYSC06). Fryer (1999) classified core collapse into three types: (a) Stars with M P 25 M make explosions and produce neutron stars.…”
Section: Introductionmentioning
confidence: 90%
“…FWH01 also computed the collapse of a rotating star with 300 M under Newtonian gravity and showed that it has a weak bounce and then recollapses to a black hole immediately. As for the collapse of supermassive stars with M k 5 ; 10 5 M , Linke et al (2001) found that they form black holes without bounce before becoming opaque to neutrinos.…”
Section: Introductionmentioning
confidence: 99%
“…The actual progenitor mass limits for these different scenarios are a subject of debate and depend on the explosion mechanism and the input physics. The fate of progenitors more massive than 75 M differs from the usual Fe-core collapse scenario by the appearance of the pairinstability, as studied by Fryer et al (2001), Linke et al (2001), , Nomoto et al (2005), Ohkubo et al (2006) and Nakazato et al (2007).…”
Section: Article Published By Edp Sciencesmentioning
confidence: 98%
“…To accelerate 570M the collapse, we depleted the pressure by 1% initially. During the evolution, we adopted a G-law equation of state according to , where denotes the specific internal energy P p (G Ϫ 1)re e of the fluid, thereby treating the gas as an ideal, adiabatic fluid in which cooling can be ignored on a dynamical timescale (Linke et al 2001).…”
Section: Introductionmentioning
confidence: 99%